Unlocking Development In Papua: The Reciprocal Relationship between Economic Growth and HDI Under Special Autonomy - Lefaan, Yosef; Joni, Joni; Hartiningsih, Endang; Mollet, Julius Ary; Liga, Marthen (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2026)
This study examines the bidirectional relationship between economic growth and human development in Indonesia’s Papua Region, a context characterized by persistent welfare disparities despite the implementation of Special Autonomy. Utilizing a balanced panel dataset covering Papua and West Papua provinces, the research applies a dual fixed-effects panel regression model estimated via Feasible Generalized Least Squares with Panel-Corrected Standard Errors to probe the nuanced feedback connections between Gross Regional Domestic Product (GRDP) per capita and the Human Development Index (HDI). The investigation confirms a vigorous, reciprocal, and mutually augmenting association between economic advancement and human progression, where increases in per capita GRDP significantly predict improvements in HDI, and advancements in HDI in turn drive substantial elevations in regional economic output. Beyond the core economic and human development variables, electricity consumption per capita emerges as a consistent, positive catalyst in both models, functioning as a "keystone catalyst" that simultaneously supports standard of living improvements and economic productivity. Conversely, population growth is identified as exerting a drag on per capita income, highlighting a "denominator effect," where rapid demographic expansion dilutes economic gains even as it expands the potential human capital base. The findings substantiate the existence of a virtuous cycle of development in Papua but underscore that achieving inclusive welfare outcomes requires integrated policy interventions that synchronize economic productivity, human capability enhancement, and energy infrastructure expansion.